PENERAPAN MODEL PEMBELAJARAN STAD BERBANTUAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Indrawati, Maya Susi (JURNAL BIOEDUCATION, 2021)
Student’s low learning outcomes in science lessons at SMP Negeri 3 Mukok are due to students’ passivity in learning. The teacher uses the lecturing and assignment method so that learning takes place in one direction and teacher-centered. The problem in this research is whether the application of the STAD method by using concept maps can improve the learning outcomes of class VII B students at SMP Negeri 3 Mukok? The purpose of this study was to improve student outcomes using the STAD learning method by using concept maps. The research conducted was a Classroom Action Research. The research procedure consisted of 4 stages, namely: Planning, Implementation, Observation and Reflection. The research subjects were VII B student at SMP Negeri 3 Mukok with 32 students. Data collection techniques was field notes and tests. Student learning outcomes showed an increase in the average score of students from cycle I to cycle II, from 63 to 75. While students' classical completeness increased from cycle I to cycle II, from 69% to 75% with an increase of 6%. It can be concluded that can be concluded that the application of the STAD method by using concept maps can improve learning outcomes of class VII B students at SMP Negeri 3 Mukok. In addition, the use of concept map can make students interactive and enthusiastic in learning. Concept map media can also improve student learning outcomes. Obstacles and deficiencies in the implementation of actions can be properly overcome.